PENTINGNYA PEMBERIAN ASI EKSLUSIF UNTUK MENCEGAH TERJADINYA STUNTING PADA BALITA: LITERATUR REVIEW - Sihab Sihab; Miftahul Falah (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Stunting is an indicator of linear growth failure caused by chronic malnutrition, repeated infections, and low stimulation in early life. This condition has long-term impacts on child development, including cognitive impairment, the risk of chronic disease, and decreased productivity in adulthood. One of the main protective factors in preventing stunting is exclusive breastfeeding for the first six months of life. This literature review aims to analyze the relationship between exclusive breastfeeding and stunting incidence based on five articles published between 2014 and 2023. A literature search was conducted through the Google Scholar database using the keywords